2018
DOI: 10.1596/1813-9450-8459
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Individual Wellbeing Through Test Scores: Evidence from a National Assessment in Mexico

Abstract: We construct two longitudinal datasets that record students' test scores in a national standardized exam in Mexico and track students from the end of primary (Grade 6) to the end of lower (Grade 9) and upper (Grade 12) secondary school, then to university and labor market participation up to two years after graduation from upper secondary. Our results show that test scores are a strong predictor of future education and labor market outcomes. Using a large sample of twins in our data, we show that the relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 3 publications
0
6
0
2
Order By: Relevance
“…5 The use of ENLACE in the CM program possibly increased teacher effort, but as SEP required the use of external proctors, it is unlikely that teachers were able to directly manipulate student responses. Previous work (Avitabile andde Hoyos, 2018, De Hoyos et al, 2018) has shown that ENLACE tests in primary education are correlated with later learning and labor market outcomes.…”
Section: Enlace Testsmentioning
confidence: 98%
“…5 The use of ENLACE in the CM program possibly increased teacher effort, but as SEP required the use of external proctors, it is unlikely that teachers were able to directly manipulate student responses. Previous work (Avitabile andde Hoyos, 2018, De Hoyos et al, 2018) has shown that ENLACE tests in primary education are correlated with later learning and labor market outcomes.…”
Section: Enlace Testsmentioning
confidence: 98%
“…Hoyos, Estrada, and Vargas used the longitudinal datasets of students' test scores in a national standardized exam in Mexico [17]. During this process, the authors track students from grade 6 through grade 12.…”
Section: Literature Review On Academic Achievementsmentioning
confidence: 99%
“…Besides, we also include other factors that may explain the variation of the test scores in 2011. For example, the test scores in grade six are essential predictors of lower-and upper-secondary on-time graduation and are the test scores as well generated from the results of De Hoyos, Estrada, and Vargas (2018) [18]. As a result, we add the test scores in 2010 when the students are in grade six to explore further.…”
Section: Elance Data and Modelmentioning
confidence: 99%
“…Los componentes que determinan el logro académico se clasifican en cuatro y se mencionan de acuerdo con el orden de relevancia determinado por el estudio: características individuales, recursos escolares, entorno institucional y antecedentes familiares, este último podría explicarse porque el entorno familiar podría ser más importante en edades más tempranas del desarrollo y menos en los jóvenes de 17 años y de más edad que cursan el tercer año de bachillerato. De Hoyos, Estrada & Vargas (2018) muestran que los puntajes de las pruebas estandarizadas para México son un fuerte predictor de la educación futura y los resultados del mercado laboral, los cuales van más allá de los antecedentes familiares.…”
Section: Revisión De Literaturaunclassified